OPTIMALISASI POTENSI DESA GUNA MENJADI DESA WISATA YANG BERSIH DAN ASRI PADA DESA PERKEBUNAN BUKIT LAWANG - Azzahra Putri Hermaya; Dayana Agustina; Erni Widiastuti; Fadhila Andini; M. Ikhsan Harahap (Jurnal Bina Bangsa Ekonomika, 2024)
The river in Bukit Lawang Plantation Village is also one of the tours that are in great demand by visitors. Institutions and communities there always participate and direct the community in preserving the environment. This research belongs to the type of qualitative research. This research methodology, which includes the use of qualitative approaches with descriptive methods, observation, interviews, and literature studies, will enable the author to investigate in depth the potential of beautiful tourism villages in Bukit Lawang Plantation and formulate relevant recommendations for sustainable tourism development. The Waste Bank or Sumatra Trashbank is a form of community concern for the environment of Bukit Lawang Village where the volume of incoming waste is more compared to what is sorted. Not a waste management initiative, but also a significant step in the development of a sustainable tourism village in Bukit Lawang Plantation.